2017
DOI: 10.7554/elife.29742
|View full text |Cite|
|
Sign up to set email alerts
|

Paradoxical response reversal of top-down modulation in cortical circuits with three interneuron types

Abstract: Pyramidal cells and interneurons expressing parvalbumin (PV), somatostatin (SST), and vasoactive intestinal peptide (VIP) show cell-type-specific connectivity patterns leading to a canonical microcircuit across cortex. Experiments recording from this circuit often report counterintuitive and seemingly contradictory findings. For example, the response of SST cells in mouse V1 to top-down behavioral modulation can change its sign when the visual input changes, a phenomenon that we call response reversal. We deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 41 publications
6
74
1
Order By: Relevance
“…The interaction between these neuron types has been recently implicated, among other phenomena, in the top-down modulation of activity during locomotion [46; 47; 48; 49; 50]. In particular, the observed change of modulation with context (dark vs visual stimuli) has been explained with a rate model with supralinear f − µ curve, assuming a change in baseline activity (low vs high) [51]. As we have shown in the present work, other scenarios exist close to response onset in networks of spiking neurons, which might lead to alternative explanations of the observed phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between these neuron types has been recently implicated, among other phenomena, in the top-down modulation of activity during locomotion [46; 47; 48; 49; 50]. In particular, the observed change of modulation with context (dark vs visual stimuli) has been explained with a rate model with supralinear f − µ curve, assuming a change in baseline activity (low vs high) [51]. As we have shown in the present work, other scenarios exist close to response onset in networks of spiking neurons, which might lead to alternative explanations of the observed phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Activating these neurons may also regulate activity within the local network, where CC neurons make contacts onto other CC neurons, as well as CT and PT cells (Mercer A et al 2005;Brown SP and S Hestrin 2009). Moreover, by increasing the activity of VIP+ interneurons, D1-Rs can disinhibit the local network, which is known to play an important role in cortical function, including within the PFC (Wang XJ et al 2004;Garcia Del Molino LC et al 2017;Kamigaki T and Y Dan 2017). Thus, D1-Rs can activate both excitatory circuits in deep layers and disinhibitory circuits in superficial layers.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that depending on the degree of viral expression, the average response of the infected neurons can decrease or increase with the light intensity: it decreases only if a large proportion of the population is infected. (Del Molino et al 2017) showed that due to the nonlinearity in the neuronal transfer function, the response of the network to stimulation can be different for different https://docs.google.com/document/d/1UaHERm5J7ZX8fMIoyG42_mFfOzWPZq32QDjE_gxdSgk/edit?ts=5c9dfa46# 27/46 background rates. In particular, they showed that it can reverse the response of SOM neurons to VIP stimulation.…”
Section: Comparison With Previous Theoretical Workmentioning
confidence: 99%